Educational Supervision Pedagogy in the Post COVID-19 for Sustainaing Development - Hiliya, Abubakar Abbas (EDUMALSYS Journal of Research in Education Management, 2024)
This paper discussed educational supervision pedagogy in the post COVID-19 era for sustainable education. Meaning of the key words such as education supervision, pedagogy, COVID-19 era and sustainable education were defined after an introduction of the main topic. A discussion of the difference was made educational supervision pedagogy before and after COVID-19 such as in-person observation and feedback for teachers, as well as face-to-face professional development sessions and use of online platforms. Relationship between educational supervision pedagogy and sustainable education were giving to include Project-based learning and Integration of sustainability principles. Problems of educational supervision after COVID-19 were listed to include; supervisors not having knowledge of how to support teachers and students in the transition from face-to-face to online teaching and how to focus on addressing the needs of teachers while engaged in online teaching. Suggestions such as Supervisors need to have all the skills and knowledge needed before taking up the role of school supervisors. Those that are already in it should go for training and retraining from time to time to expand their skills, knowledge and development, they should find out ways in which they can support teachers at any point in time. This will in turn enable the teachers to attend to students effectively.